Rutinitas Aktivitas Fisik di Tengah Pandemi Corona Virus Disease (Covid)-19 Siswa SMP Negeri Se-Kecamatan Semarang Selatan Tahun 2020 - Farah Nur Oktavia; Rumini Rumini (Universitas Negeri Semarang, 2022)
The problem of this research is how is the routine of physical activity in the midst of the Covid-19 pandemic for state junior high school students in South Semarang District in 2020? This type of research is a type of quantitative descriptive research, using a survey method. The population of junior high school students in South Semarang District, with a research sample of 326 students. The method of analysis is quantitative. The results showed that the physical activity of South Semarang State Junior High School students in 2020 which was carried out for the last seven days during the current pandemic was in the very high category, none at all, in the high category 7 students, in the medium category with 68 students, in the low category by 206 students, and in the low category by 206 students. very low there are 45 students. Repetition in 1 week very often there is only 1 student, repetition in 1 week there are often 6 students. The results of repetition of this type of physical activity in 1 week are quite often 38 students, repetition in 1 week sometimes there are 178 students with repetition in 1 week there are never 103 students. The conclusion of the research on routine physical activity in the midst of the COVID-19 pandemic is still low.